Fiscal sustainability and economic growth in the light of new economic governance - Južnik Rotar, Laura (Technological and Economic Development of Economy, 2025)
This research estimates the effects of public debt on economic growth. In addition, it contributes to examining the impact of public debt on investment as a possible channel of impact on economic growth. The empirical analysis is based on a smooth transition panel data regression model. The results show the non-linear relationship between public debt and economic growth for the sample of 12 Euro area countries is markedly statistically significant. The sustainable threshold for this relationship is on average between 93% and 105%. This implies that public debt to gross domestic product ratios above this sustainable threshold would have a negative effect on economic growth. Although insignificant, the results for the sample of 20 Euro area countries could indicate that for the less developed Euro countries the potentially negative effects of high debt can already be seen at a lower level of public debt, which is the case for even more sensible debt reduction policies. Taking into consideration the fiscal rules, the results suggest that one size does not necessarily fit all. Moreover, the trade-off between fiscal consolidation and increased green public investment will be one of the key challenges of this decade given the reinstated European Union fiscal rules. First published online 16 April 2025